Karakteristik Hukum Islam dan Asas Penerapannya - Mahmudin Mahmudin (STAI AL FALAH Banjarbaru, 2021)
The religion of Islam revealed by Allah SWT has a goal, namely to realize the benefit of human life individually and in society. So are the laws. Islamic law emphasizes the final goal, which is to realize the human benefit. This function can include social engineering functions. Islamic law is produced to realize the benefit and progress of the community. To realize this and in a larger capacity, it can be through the siyasa syariyyah process, with the product of qanun or legislation, changes for a better purpose. This means that it is very likely to change if the consideration of the benefits for the community arises. Broadly speaking, the nature and characteristics of Islamic law are Arrabbaniyah (Divinity) Asy-Syumûl (Universal) al-Jam'u Baina al-Murûnah wa Tsabath (Combining flexibility and stability), Al-Yusru wa Raf'u al-Haraj fî as -Syariah al-Islâmiyah (Islamic Shari'a makes it easy, and eliminates difficulties).Keywords: Evaluation, Accuracy of Distance Learning Media Selection.